Seventeenth-Century Fiction : Text and Transmission - Edited by Glomski, Jacqueline and Moreau, Isabelle (New York Oxford University Press, 2016)
A multi-authored study of the emergence and transmission of fictional writing in in Europe in the seventeenth century, with the aim of improving understanding of the origins of the novel.
Include Bibliography and Index
Keywords: Fiction